History of the emblem of the International Islamic University Malaysia - Hassan @ Mohamed, Nor Jana (OFIIR-CENTRIS, 2024)
The original draft of the IIUM logo was designed and encapsulated from the vision and mission of Professor Dr. Mohd. Kamal Hassan, who then served as IIUM’s third Rector. The artwork’s completion was on January 16th, 1985. Professor Kamal wrote the IIUM’s concept paper on February 11th, 1982, and May 20th, 1983, is the establishment date of the University. People can view the original artwork at the M. Kamal Hassan Memorial Library, Level 4, M. Abdul Rauf Building, IIUM, Gombak.